2014
DOI: 10.1007/s10597-014-9707-x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Dutch Self-Sufficiency Matrix (SSM-D) to Inform Allocation Decisions to Public Mental Health Care for Homeless People

Abstract: The current study set out to develop a decision support tool based on the Self-Sufficiency Matrix (Dutch version; SSM-D) for the clinical decision to allocate homeless people to the public mental health care system at the central access point of public mental health care in Amsterdam, The Netherlands. Logistic regression and receiver operating characteristic-curve analyses were used to model professional decisions and establish four decision categories based on SSM-D scores from half of the research population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 16 publications
2
14
0
4
Order By: Relevance
“…For instance, some assessment tools, such as the Vulnerability Assessment Tool (Downtown Emergency Service Center, ), aim to prioritize housing units based on vulnerability , that is, the likelihood a person will experience harm or death if they remain homeless. In contrast, other assessments, such as the SSM, aim to determine one's housing support service needs based upon their self‐sufficiency , that is, the capability and achievement of an acceptable level of functioning either by oneself or by adequately organizing the help and support of care providers (Lauriks et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, some assessment tools, such as the Vulnerability Assessment Tool (Downtown Emergency Service Center, ), aim to prioritize housing units based on vulnerability , that is, the likelihood a person will experience harm or death if they remain homeless. In contrast, other assessments, such as the SSM, aim to determine one's housing support service needs based upon their self‐sufficiency , that is, the capability and achievement of an acceptable level of functioning either by oneself or by adequately organizing the help and support of care providers (Lauriks et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…They found that participants with greater scores on the SSM‐D (i.e., grater self‐sufficiency) were less likely to display a need for care, indicating that it may be an effective tool for service provision allocation. Additional research revealed all domains included in the SSM‐D were found to be necessary and nonredundant for the construct of self‐sufficiency (Lauriks et al, ). Taken together, these findings provide potential evidence for the use of the SSM and SSM‐D as decision support tools for public mental health care and housing services.…”
Section: Introductionmentioning
confidence: 99%
“…A população que vive na rua é composta por pessoas de ambos os sexos, de diferentes idades, solteiras, casadas, que vivem sozinhas, com familiares ou com amigos, com diversos problemas de saúde e tendo várias ocupações (Lauriks et al, 2014).…”
Section: Introductionunclassified
“…Tais circunstâncias adversas se tornam ainda mais intensas quando se trata de mulheres, parcela minoritária que compõe esse grupo social (Lauriks et al, 2014;Rosa e Bretas, 2015).…”
Section: Introdução 19unclassified
See 1 more Smart Citation